High-resolution elemental localization in vacuolate plant cells by nanoscale secondary ion mass spectrometry. - Smart, K; Smith, J; Kilburn, MR; Martin, BG; Hawes, C; Grovenor, C (2010)
By combining the capabilities of advanced sample preparation methodologies with the latest generation of secondary ion mass spectrometry instrumentation, we show that chemical information on the distribution of even dilute species in biological samples can be obtained with spatial resolutions of better than 100 nm. Here, we show the distribution of nickel and other elements in leaf tissue of the nickel hyperaccumulator plant Alyssum lesbiacum prepared by high-pressure freezing and freeze substitution.